National Work-Family Policies and Gender Earnings Inequality in 26 OECD Countries, 1999 to 2019 - Jennifer L. Hook; Meiying Li (Socius)
The authors investigate whether work-family policies help incorporate women into the labor market, but exacerbate the gender earnings gap and motherhood penalty, especially for mothers and/or tertiary-educated women. The authors use repeated cross-sectional income data from the Luxembourg Income Study database (1999–2019) ( n  = 26 countries, 280 country-years, 2.9 million employees) combined with an original collection of indicators on work-family policies, labor market conditions, and gender norms. The authors find that only one work-family policy, long paid parental leave (longer than six months), is associated with a larger gender earnings gap for mothers and tertiary-educated women. The negative relationship between long paid leave and women’s earning percentile is not well explained by selection, full-time status, work hours, experience, occupation, or sector, suggesting discrimination mechanisms. These findings add to the growing evidence that long paid leave specifically, as opposed to work-family policies more generally, cleaves the labor market outcomes of women from men.